Development of a Targeted Welding Point System for Robotic Trainers to Increase Automated Welding Precision - Shamri, Shaza Nur Iman; Hehsan, Haffidzudin; Md Salleh, Salihatun (Progress in Engineering Application and Technology, 2025)
This study presents the development of a Targeted Welding Point System(TWPS) to aid in the precision and efficiency. The TWPS investigates how to reduce processing time while improving operational efficiency by addressing three challenges: robotic kinematic limits, environmental unpredictability, and inefficient path selection. Despite advancements in robotic automation, many educational settings still lack affordable and practical tools to train students effectively. trajectory optimization training and understanding robotic movement in angle-oriented environments limits student readiness for industrial automation deployment. In today’s era, in the industrial field, whether an engineer or a machinist, both theoretical knowledge and practical skills are required. The objective of study addresses key challenges in robotic automation, such as inefficient trajectory planning and limited practical training tools in TVET environments. The proposed method involves testing motions at various angular arrangements using a programmable robotic arm, which mimics industrial welding processes. By examining time efficiency across angles (0°, 30°, 60°, and 90°), the study shows how trajectory complexity affects system performance. Participants in the training displayed significant increases in control of accuracy. students took longer to complete the sequence of welding points at the beginning. By the final point, the average time decrease, indicating improved understanding and control of the robotic system. angles demand more joint reorientation and time, leading to reduced efficiency. Collaborating with industries helps us validate the TWPS in real manufacturing conditions, ensuring it works effectively in practical use.